Michael F. Strmiska, ed. Modern Paganism in World Cultures: Comparative Perspectives - Bado-Fralick, Nikki (Pomegranate, 2007)
Michael F. Strmiska, ed. Modern Paganism in World Cultures: Comparative Perspectives (Santa Barbara, CA: ABC-CLIO, 2005), 382 pp., 85.00 (cloth) 105 (ebook).